THE EFFECTIVENESS OF SELF CHECK-IN AND BAGGAGE CHECK-IN ON PASSENGER SATISFACTION AT SOEKARNO HATTA AIRPORT - Sucipto, Yuwono D.; Saidah, Deslida; Jusuf, Angela Vanessa; Fitri, Fasya Rahma (JMMS - JURNAL MANAJEMEN MANDIRI SABURAI, 2025)
In Indonesia, one of the busiest international airports is Soekarno-Hatta International Airport, and it often faces a significant increase in passenger numbers, which in turn causes long queues at manual check-in counters. This research aims to examine the impact of using self check-in machines on the effectiveness and satisfaction of passengers at Soekarno-Hatta Airport. In this study, the population that is the focus is passengers at Soekarno-Hatta Airport, with a sample of one hundred (100) people taken using nonprobability sampling techniques via accidental sampling, especially those who have used self check-in machines. This research method is quantitative with SEM-PLS data analysis techniques which are used to predict and develop research. The results of this research reveal that Self Check-in Machines can reduce waiting time, increase passenger satisfaction, and increase the efficiency of the check-in process.